Pupillary response to moving stimuli of different speeds - Yuexin Wang; Yining Guo; Jiajia Wang; Ziyuan Liu; Xuemin Li (Bern Open Publishing, 2021)
Purpose: To investigate the pupillary response to moving stimuli of different speeds and the influence of different luminance environments. Methods: Twenty-eight participants with normal or corrected-to-normal vision were included. The participants were required to track moving optotypes horizontally, and their pupils were videoed with an infrared camera. Stimuli of different speeds were presented in different luminance environments. Results: Experiment 1 demonstrated that the motion stimuli induced pupil dilation in a speed-dependent pattern. The pupil dilation increased as the speed increased, and the pupil dilation gradually increased, then reached saturation. Experiment 2 showed that a stimulus targeting the rod- or cone-mediated pathway could induce pupil dilation in a similar speed-dependent pattern. The absolute but not relative pupil dilation in the cone paradigm was significantly larger than that in the rod paradigm. As the speed increased, the pupil dilation in the cone paradigm reached saturation at speed slower than the rod paradigm. Conclusions: Motion stimuli induced pupil dilation in a speed-dependent pattern, and as the motion speed increased, the pupil dilation gradually increased and reached saturation. And the speed required to reach saturation in the cone paradigm was slower than in the rod paradigm.